Menarik Benang Merah Basis Pendidikan Islam Bermartabat - Dasopang, Muhammad Darwis (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2015)
Education means as a normative learning. Learning is to move situation of social relationship between educators and learner. Education is essential for improving the educational success itself. All the learning material which is delivered from religion, science, technology, arts, and culture becomes a sinergic and purposeful content in educational practice. This process becomes an effort in improving the quality of education to humaniza the learner who are responsible for themselves, family, community and nation.